Mib1 modulates dynamin 2 recruitment via Snx18 to promote Dll1 endocytosis for efficient Notch signaling. (28th February 2016) - Okano, Makoto; Matsuo, Hiromi; Nishimura, Yuya; Hozumi, Katsuto; Yoshioka, Saho; Tonoki, Ayako; Itoh, Motoyuki
Abstract: Notch signaling regulates normal development and tissue homeostasis. Ligand endocytosis plays critical roles in Notch signaling activation. Endocytic proteins such as epsin and dynamin participate in Notch ligand activity by mediating Notch ligand endocytosis. The ubiquitin ligase Mib1 also plays essential roles in Notch signaling via Notch ligand ubiquitination. However, the molecular links between Mib1 and endocytic proteins have not been fully defined. Here, we show that Mib1 is involved in dynamin 2 recruitment to Dll1 and that Snx18, which interacts with dynamin 2, modestly regulates Dll1 endocytosis. Furthermore, the ubiquitin ligase activity of Mib1 is induced by Notch ligand–receptor interactions. Mib1 promotes the interaction between dynamin 2 and Snx18 in an ubiquitin ligase activity‐dependent manner. These results suggest that Mib1 modulates dynamin recruitment by regulating the interaction between Snx18 and dynamin 2, thereby helping to ensure the efficient signaling activity of Notch ligands. Abstract : Dll1–Notch interaction promotes Mib1 ubiquitin ligase activity, and Dll1 is ubiquitinated by Mib1. The Mib1 ubiquitin ligase activity modulates the recruitment of dynamin 2 via Snx18 to the sites of Dll1 internalization and promotes Dll1 endocytosis. This process leads to mechanical dissociation of the NotchECD and the release of the NICD in adjacent cells.